Helminth-Induced Immune Regulation: Implications for Immune Responses to Tuberculosis - Chatterjee, Soumya; Nutman, Thomas B. (PLoS pathogens, 2015)
[...]adult subjects in endemic areas with chronic helminth infection show impaired cellular responses that may alter the responses to Mtb antigens and possibly contribute to a higher incidence of active TB disease [12]. [...]subjects with latent TB and filarial coinfection have been shown to exhibit decreased toll-like receptor 2 (TLR2) and toll-like receptor 9 (TLR9) expression, which was reversed after successful antifilarial chemotherapy [30].\n Using the diagnostic tools available to these investigators, the rates of acquisition of parasitic infection by infants enrolled in this study were very low, suggesting that helminth-induced T cell priming at birth may have long-lasting consequences for immunologic memory.